Improving the athletic training of open water swimmers: the role of multicomponent training - Mannanov E.I.; Mannanov A.I. (Theory and Practice of Physical Culture, 2025)
Objective of the study was to evaluation of the effect of multifaceted variations in training regimens on enhancing the physical and tactical abilities of swimmers in open water. Methods and structure of the study. The research is grounded on the assumption that training with programs that consider multi-faceted environmental alterations, particularly incorporating open water training, can substantially enhance the physical endurance, tactical abilities, and psychological resilience of swimmers. In this investigation, the performance of two groups of swimmers was assessed: the first group adhered to the conventional program in the pool, while the second group incorporated open water sessions with various exercises. A total of 40 swimmers, with diverse levels of training and expertise in open water swimming, participated in the experiment. Results and conclusions. The study’s outcomes support the theory that incorporating training in open water enhances the abilities of swimmers. These results can be applied to create novel training methods designed to maximize the training of swimmers in open water environments.